Association between Adiponectin Gene Polymorphism and Environmental Risk Factors of Type 2 Diabetes Mellitus among the Chinese Population in Hohhot. (22nd June 2020) - Cui, Meng; Gao, Yumin; Zhao, Yanping; Pang, Hui; Chen, Le; Wang, Zhidi; Zhao, Lingyan; Li, Minhui
Abstract : Objective . The aim of this study was to investigate the association between adiponectin gene polymorphisms rs10937273, rs1501299, rs182052, rs2241767, and rs266729 and environmental risk factors of type 2 diabetes mellitus (T2DM) in Hohhot. The study explored different models of gene-environment interactions, aimed at providing approaches for the prevention and control of T2DM in combination with the characteristics of the local population. Methods . A case-control study was conducted including 406 Chinese participants, comprising 203 cases and 203 controls from various hospitals. Adiponectin ( ADIPOQ ) gene polymorphisms rs10937273, rs1501299, rs182052, rs2241767, and rs266729 were detected using an improved multiple ligation detection reaction technique. Generalized multifactor dimensionality reduction (GMDR) and logistic regression were conducted to analyze the associations between adiponectin gene polymorphisms and T2DM, as well as the interactions between adiponectin gene polymorphisms and environmental factors. Results . ADIPOQ gene polymorphisms rs10937273, rs1501299, rs182052, rs2241767, and rs266729 were associated with type 2 diabetes. Based on the haplotype of the five adiponectin gene single-nucleotide polymorphism (SNP) loci, we found that G-G-A-A-C was a susceptible haplotype of T2DM (P < 0.05 ). Interaction analyses demonstrated associations between rs1501299 and central obesity (consistency = 80 %, P = 0.011 ) and between rs266729 and rs182052 and central obesity (consistency = 70 %, P = 0.011 ). Conclusions . Our findings indicate that there is an interaction between the ADIPOQ gene and central obesity, which provides new insights into the prevention and treatment of T2DM.